(untitled) - Shaner, Roderick (Baltimore, 1997)
This book is a concise summary of psychiatric diagnses, guidelines for psychiatric treatment, and important psychiatric facts.
Keywords: Psychiatry,Psychiatry,Mental disorders; Examination questions